Perangkat Lunak Administrasi Pengajuan Judul Penelitian Pada Sekolah Tinggi Teknologi Pagar Alam - Siti Muntari (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2016)
Along with the rapid advances in information technology, in various aspects of life in menmanfaatkan technological advances, especially in Negri and private universities as well as in the process of filing the title penelitian.Tujuan of the writing of this research is to design the administrative system of filing titles Online research using PHP program and MySQL database at the College of Technology Pagar Alam (STTP). The methodology used is Web Engineering (web engineering), the desired result is the availability of support systems for online submission of research titles which can be obtained without having to come kekampus to apply for the title of the study, could be done dimanpun origin is connected to the Internet network.